2000
DOI: 10.1038/sj.bmt.1702173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of marrow and blood cell yields from the same donors in a double-blind, randomized study of allogeneic marrow vs blood stem cell transplantation

Abstract: Summary:Forty healthy adult donors underwent marrow (BM) as well as peripheral blood (PBSC) stem cell collections for their HLA-identical adult siblings with hematologic malignancies. BM was harvested on day 1 (target 3 ؋ 10 8 nucleated cells/kg, 10 g/kg lenograstim (glycosylated G-CSF) administered on days 2-6, and a single leukapheresis performed on day 6. The blood volume processed was the higher of 200% donor blood volume or 10 liters. The total nucleated cell (TNC) yields from PBSC were 1.1-to 4.3-fold hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
(9 reference statements)
1
36
0
1
Order By: Relevance
“…However, over the last few years mobilized peripheral blood has been used as an alternative source of stem cells for allogeneic transplantation. In adult patients, several retrospective and prospective randomized studies comparing allogeneic blood and bone marrow transplantation have indicated that allo-PBPCT is better than BMT in terms of engraftment kinetics and immune recovery with a similar incidence of acute GVHD, [7][8][9][10][11][12]24 although, issues regarding chronic GVHD incidence are still unresolved. In addition, two recent randomized studies have suggested a potential benefit for allo-PBPCT with respect to relapse and survival without an increased incidence of cGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, over the last few years mobilized peripheral blood has been used as an alternative source of stem cells for allogeneic transplantation. In adult patients, several retrospective and prospective randomized studies comparing allogeneic blood and bone marrow transplantation have indicated that allo-PBPCT is better than BMT in terms of engraftment kinetics and immune recovery with a similar incidence of acute GVHD, [7][8][9][10][11][12]24 although, issues regarding chronic GVHD incidence are still unresolved. In addition, two recent randomized studies have suggested a potential benefit for allo-PBPCT with respect to relapse and survival without an increased incidence of cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the results of other studies of allo-PBPCT in either adults or children. [7][8][9][10][11][12][24][25][26][27] A possible explanation for this may be the larger numbers of committed progenitors in cytokine-mobilized peripheral blood. As with another matched-pair analysis recently published, 27 we found no relationship between the CD34 ϩ cell dose and neutrophil engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed a randomized, double-blind study comparing allogeneic BMT and PBSCT in hematologic malignancies. 20 With the availability of prospectively collected data of the various cell subpopulations constituting the graft, 21 we attempted to examine the relationship between the number of CD34 ϩ cells infused and TRM.…”
mentioning
confidence: 99%
“…Patients transplanted with blood stem cells had better outcomes as regards disease-free survival and overall survival. 51 Whether the improvement was related to the larger number of stem/progenitor cells in a blood stem cell vs a marrow stem cell graft product 52 was neither discounted nor demonstrated. A second smaller randomized study of allogeneic marrow vs mobilized blood stem cell transplantation found that patients who received fewer than 2 Â 10 6 /kg CD34+ cells, regardless of the cell source, experienced higher mortality and poorer survival.…”
Section: Mobilization Efficiency and Outcomementioning
confidence: 99%